Documents in international environmental law - Sands, Philippe, 1960-; Galizzi, Paolo (Cambridge : Cambridge University Press, 2004)
Documents in International Environmental Law is the companion volume to the second edition of Philippe Sands' Principles of International Environmental Law. It comprises a representative selection of international environmental treaties and documents which are essential for anyone interested in international law in the field of environmental protection. This edition represents an up-to-date collection of the most important documents and aims to make the text and the key information on the legal status of the various acts, including its parties where a treaty is concerned, easily accessible to students, academics and practitioners. Each document is introduced with a short Editorial Note, summarising the main provisions of the instrument and places it in its wider context. Editorial notes are followed by information on the date of adoption/signature of the document, its entry into force and a list of the parties (if a treaty).
I. General instruments -- II. Atmosphere -- IIIa. Oceans: global -- IIIb. Oceans: regional -- IV. Freshwater resources -- V. Biodiversity -- VIa. Hazardous substances and activities: nuclear -- VIb. Hazardous substances and activities: pesticides -- VIc. Hazardous substances and activities: waste -- VII. Human rights and the environment -- VIII. War and the environment -- IX. Trade and the environment -- X. Environmental impact assessment and access to information -- XI. Liability for environmental damage and breaches of environmental obligations -- XII. The Antarctic.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Environmental law, International -- History -- Sources